2018
DOI: 10.1038/s41398-018-0236-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of self-reported risk-taking behaviour, trans-ethnic consistency and relevance to brain gene expression

Abstract: Risk-taking behaviour is an important component of several psychiatric disorders, including attention-deficit hyperactivity disorder, schizophrenia and bipolar disorder. Previously, two genetic loci have been associated with self-reported risk taking and significant genetic overlap with psychiatric disorders was identified within a subsample of UK Biobank. Using the white British participants of the full UK Biobank cohort (n = 83,677 risk takers versus 244,662 controls) for our primary analysis, we conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 64 publications
2
23
1
Order By: Relevance
“…In addition, the association of this region with risk-taking is novel. Although it has previously been demonstrated that genetic regulation of risk-taking overlaps with that for schizophrenia, and CNTN4 has previously been associated with schizophrenia [12,40], the null association between schizophrenia-associated SNPs and risk-taking in this study suggests that the signals for these traits are independent.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, the association of this region with risk-taking is novel. Although it has previously been demonstrated that genetic regulation of risk-taking overlaps with that for schizophrenia, and CNTN4 has previously been associated with schizophrenia [12,40], the null association between schizophrenia-associated SNPs and risk-taking in this study suggests that the signals for these traits are independent.…”
Section: Discussioncontrasting
confidence: 75%
“…GWAS meta-analysis of sun-seeking data in 261,915 subjects from the UK Biobank and the Harvard cohorts identified five genetic loci involved in sun-seeking behavior: TMEM182, CADM2, MIR2113, MTMR2/CEP57/FAM76B, and PLCL1/LINC01923/SATB2. All the five genetic loci have previously been identified in GWAS for behavioral traits and addiction (Clifton et al, 2018;Erzurumluoglu et al, 2019;Hill et al, 2019;Karlsson Linnér et al, 2019;Lee et al, 2018;Nagel et al, 2018a;Pasman et al, 2018;Savage et al, 2018;Strawbridge et al, 2018), educational attainment (Lee et al, 2018;Okbay et al, 2016), personality traits (Nagel et al, 2018a), or cognitive function (Davies et al, 2015;Lam et al, 2017;Lee et al, 2018;Nagel et al, 2018a). Moreover, both the microRNA MIR2113 and the long noncoding RNA (lncRNA) LINC01923 identified in the study are likely involved in the wider regulation of addiction traits such as smoking and alcohol and drug use.…”
Section: Discussionmentioning
confidence: 99%
“…All associated loci pinpointed genes (TMEM182, CADM2, MIR2113, MTMR2/CEP57/FAM76B, and PLCL1/LINC01923/ SATB2) that have previously been linked by GWASs to behavioral traits including addiction (Clifton et al, 2018;Erzurumluoglu et al, 2019;Hill et al, 2019;Karlsson Linnér et al, 2019;Lee et al, 2018;Liu et al, 2019;Nagel et al, 2018a;Pasman et al, 2018;Savage et al, 2018;Strawbridge et al, 2018), personality traits (Nagel et al, 2018a), cognitive function (Davies et al, 2015;Lam et al, 2017;Lee et al, 2018;Nagel et al, 2018a), or educational attainment (Lee et al, 2018;Okbay et al, 2016). Moreover, they are in LD with variants also associated with those traits ( Supplementary Table S9).…”
Section: Functional Characterizationmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in the locus encoding the synaptic cell adhesion molecule 2 ( CADM2 ) on chromosome 3 have been associated with a number of psychological traits, including educational attainment 3 , alcohol consumption 4 , cannabis use 5 , physical activity habits 6 , risk-taking behaviour 7,8 , attention-deficit/hyperactivity disorder 9 and obesity 10 . Several lines of evidence point to CADM2 being the gene through which SNPs are having their effects, including genotype-specific effects on CADM2 mRNA expression levels 7,8 , C ADM2 being predominantly expressed in the brain, and cadm2 knockout models demonstrating relevant phenotypes. Specifically, cadm2 -knockout mice have reduced adiposity, reduced systemic glucose levels, improved insulin sensitivity, increased locomotor activity, increased energy expenditure rate and raised core body temperature, suggesting an important role in systemic energy homeostasis 11 .…”
Section: Introductionmentioning
confidence: 99%